OPTOELECTRONIC THREE-WAVE MOISTURE METER OF RAW COTTON - ORIPOV, JASURBEK; Kuldashov, Golibjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The article provides information on the development of a tricolor LED emitter of the middle infrared region of the spectrum, consisting of a measuring LED chip for fibers with a wavelength of 1.8 microns, a measuring LED chip for water with a wavelength of 1.94 microns and a reference LED chip with a wavelength of 2.2 microns, as well as an optoelectronic three-wave moisture meter raw cotton developed on the basis of this tricolor LED emitter. To improve the accuracy of measuring the moisture content of raw cotton, an optoelectronic three-wave moisture meter has been developed, the presence of three radiation channels allows not only simultaneously monitoring the optical absorption of water and the physicochemical properties of cotton fibers. The moisture meter consists of an exponential voltage shaper, three emitting diodes (emitting at reference, measuring wavelengths and at a wavelength lying in the absorption band of uninformative parameters), a controlled object, a photodetector and a photoelectric signal processing unit.